Soumission: A Phenomenology of Academia - Alfaro Vargas, Roy (2018)
Michel Houllebecq’s Soumission is analyzed in relation to its central character François, to describe the dialectics between neoliberal and phenomenological hedonism and economic issues, as a critique of academia, in the context of the current crisis of capitalism. The analysis also allows the elaboration of a realist-dialectical poetics regarding the cognitive estrangement of science fiction and the realism of Balzac, Zola, and Flaubert, to counteract the politics of the impossible developed in unnatural narratives and the technocratic novum.